CD13 Regulates Anchorage and Differentiation of the Skeletal Muscle Satellite Stem Cell Population in Ischemic Injury. (23rd May 2014) - Rahman, M. Mamunur; Ghosh, Mallika; Subramani, Jaganathan; Fong, Guo-Hua; Carlson, Morgan E.; Shapiro, Linda H.
Abstract: CD13 is a multifunctional cell surface molecule that regulates inflammatory and angiogenic mechanisms in vitro, but its contribution to these processes in vivo or potential roles in stem cell biology remains unexplored. We investigated the impact of loss of CD13 on a model of ischemic skeletal muscle injury that involves angiogenesis, inflammation, and stem cell mobilization. Consistent with its role as an inflammatory adhesion molecule, lack of CD13 altered myeloid trafficking in the injured muscle, resulting in cytokine profiles skewed toward a prohealing environment. Despite this healing-favorable context, CD13 KO animals showed significantly impaired limb perfusion with increased necrosis, fibrosis, and lipid accumulation. Capillary density was correspondingly decreased, implicating CD13 in skeletal muscle angiogenesis. The number of CD45−/Sca1−/α7-integrin+/ β 1-integrin+ satellite cells was markedly diminished in injured CD13 KO muscles and adhesion of isolated CD13 KO satellite cells was impaired while their differentiation was accelerated. Bone marrow transplantation studies showed contributions from both host and donor cells to wound healing. Importantly, CD13 was coexpressed with Pax7 on isolated muscle-resident satellite cells. Finally, phosphorylated-focal adhesion kinase and ERK levels were reduced in injured CD13 KO muscles, consistent with CD13 regulating satellite cell adhesion, potentially contributing to the maintenance and renewal of the satellite stem cell pool and facilitating skeletal muscle regeneration. Stem Cells 2014;32:1564–1577